THE ANALYSIS OF THE IMPACT OF WORKING-AGE POPULATION ON INDONESIAN LABOUR - Muhammad Arif; Rosni Rosni; Zukya Rona Islami; M Taufik Rahmadi (JURNAL GEOGRAFI, 2021)
The population is a very interesting object of study. It is because human is the main actor in economic activity, especially in terms of the labor force. The population as a workforce is one aspect of the factors of production that will contribute to the economic growth in a particular region. If the working-age population and non-working age population is well facilitated, including the enactment of government policies regarding improving their productivity, the population growth would benefit the regional economy. Indonesia is a country with a large population so that it potentially has a large workforce for economic development. Therefore, this research aims to examine the effect of the working-age population on the labor force in Indonesia. To achieve this goal, this research uses a literature review method. The data used in this study is secondary data obtained from BPS and BAPPENAS publications, books, and research articles. The discussion in this paper describes the development of the productive age population, employment issues in Indonesia, and the effect of the working-age population on employment in Indonesia. in conclusion, the high number of populations of productive age (demographic bonus) does not immediately occur. The working-age population greatly influences the workforce in Indonesia. The researchers hope that this article can be a reference for similar research in the future.Keywords: analysis, population, working-age, employment, IndonesiaPermasalahan kependudukan sangat menarik untuk dikaji dan dianalisis. Hal ini dikarenakan penduduk khususnya manusia merupakan pelaku utama dalam kegiatan ekonomi termasuk dalam hal ketenagakerjaan. Penduduk sebagai tenaga kerja merupakan salah satu variabel dalam faktor produksi yang akan mempengaruhi pertumbuhan ekonomi di suatu wilayah. Bila komposisi penduduk usia produktif dan yang belum produktif dipfasilitasi dengan baik, termasuk adanya kebijakan pemerintah yang menfokuskan pada kemajuan produktivitas mereka, maka pertumbuhan penduduk dengan komposisi yang demikian akan menguntungkan perekonomian daerah tersebut. Indonesia merupakan salah satu negara dengan jumlah penduduk yang banyak sehinnga berpotensi memiliki tenaga kerja yang banyak untuk kemajuan ekonomi. Oleh karena itu, penelitian iin bertujian untuk menalaah pengaruh jumlah penduduk usia produktif terhadap kondisi ketenagakerjaan di Indonesia.  Agar tujuan peneliti tercapai, peneliti menggunakan metode kajian pustaka. Data yang digunkan adalah data sekunder yang diperoleh dari publikasi BPS, BAPPENAS, buku serta artikel penelitian yang relevan dengan tema kajian penelitian. Pembahasan pada tulisan ini memaparkan mengenai perkembangan penduduk usia produktif, problematika ketenagakerjaan di Indonesia, serta pengaruh penduduk usia produktif terhadap ketenagakerjaan di Indonesia. Beberapa hal yang dapat disimpulkan yaitu, Jumlah penduduk usia produktif yang tinggi (bonus demografi) tidak langsung terjadi, Jumlah penduduk usia produktif sangat berpengaruh pada ketengakerjaan di Indonesia. Penulis berharap artikel ini dapat menjadi referensi bagi penelitian sejenis. Kata kunci: analisis, penduduk, usia produktif, ketenagakerjaan, Indonesia